(untitled) (Research, Society and Development, 2022)
This article is a literature review conducted, which aimed to identify how are developed practices that aim to develop Statistical Literacy through the STEAM Approach in Middle School, as well as to analyze which are the areas of the teachers involved in these practices. The data, from the last five years, were collected from the Google Scholar, Journals Platform of the Coordination for the Improvement of Higher Education Personnel (CAPES), the Scientific Electronic Library Online (SciELO) and the Brazilian Digital Library of Theses and Dissertations (BDTD). A description and analysis of the practices was carried out, in which the authors point out that interventions anchored in STEAM are relevant to the development of statistical literacy, favor interdisciplinarity, learning through inquiry, creative learning, and other skills considered relevant in the 21st century. It was found that such practices advocate the resolution of real problems or simulated situations. There was a predominance of mathematics teachers in the practices that partner with teachers of early grades and science teachers.